Vertical versus planar neural induction in Rana pipiens embryos. - Saint-Jeannet, J P (1994)
The neural plate in the amphibian embryo is induced in the ectoderm by signals from the dorsal mesoderm. In the extensively studied species Xenopus laevis, such signals are believed to proceed along two alternate pathways, defined as vertical and planar induction. We have studied the relative importance of these pathways in Rana pipiens. In the embryo of this frog, dorsal mesoderm involution can be diverted from its normal course by injection of peptides that inhibit interaction of fibronectin with its receptor. In such embryos, dorsal mesoderm failed to migrate across the blastocoel roof but moved bilaterally along the equator, leading to the formation of two notochords. Neural tissue differentiation occurred in close association with each notochord, but no neural tissue formed along the dorsal midline as might have been predicted by a predominantly planar induction model. While in X. laevis planar induction has been reported to be a major pathway in neuralizing the ecoderm, the results presented here indicate that vertical induction predominates in initiating neural development in R. pipiens embryos.